1983
DOI: 10.1111/j.1365-2494.1983.tb01626.x
|View full text |Cite
|
Sign up to set email alerts
|

A technique to record automatically some aspects of grazing and ruminating behaviour in sheep

Abstract: The construction of a transducer and the use of a recording system to measure jaw movements of grazing sheep is described. The time spent grazing, ruminating and idling may be measured by this equipment and the data produced automatically processed using a microprocessor which determines each minute whether the animal is grazing, ruminating or idling and also summarizes these data to give total times. The accuracy of this technique in relation to manual observation is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 10 publications
0
43
0
Order By: Relevance
“…A simple device for recording grazing activity in sheep or cattle on short swards, in terms of the lowering of the head to represent grazing, has been available for many years (Vibracorder, Kienzle Apparate GmbH, Villingen, Germany; Allden, 1962); tilt switches have also been used. Since such devices are not capable of recording individual bites, equipment has been developed to record jaw movements by various means, including pneumatic balloons, strain gauges and, more recently, a C-packed rubber tube which, upon stretching, exhibits a change in its electrical resistance (Penning, 1983). Microphones to monitor the sound of jaw activities have also been used (Laca et al 1994).…”
Section: Estimating Intake and Diet Composition From Behavioural Obsementioning
confidence: 99%
“…A simple device for recording grazing activity in sheep or cattle on short swards, in terms of the lowering of the head to represent grazing, has been available for many years (Vibracorder, Kienzle Apparate GmbH, Villingen, Germany; Allden, 1962); tilt switches have also been used. Since such devices are not capable of recording individual bites, equipment has been developed to record jaw movements by various means, including pneumatic balloons, strain gauges and, more recently, a C-packed rubber tube which, upon stretching, exhibits a change in its electrical resistance (Penning, 1983). Microphones to monitor the sound of jaw activities have also been used (Laca et al 1994).…”
Section: Estimating Intake and Diet Composition From Behavioural Obsementioning
confidence: 99%
“…Further study of the data presented by Penning (1983) and observations of grazing animals showed that jaw movements whilst the sheep were biting herbage produced signals of a lower amplitude than those associated with masticating, i.e. chewing the herbage just harvested.…”
Section: Introductionmentioning
confidence: 95%
“…On 1 d during each period, when no other experimental measurements were being taken, the sheep were fitted with jaw recorders (Penning, 1983), to record automatically each animal's chewing and ruminating activity throughout one 24 h period. The recorders were fixed to the sheep at least 30 min before the starch was administered, and were removed 24 h later.…”
Section: Methodsmentioning
confidence: 99%